2018
DOI: 10.1590/1517-869220182402179200
|View full text |Cite
|
Sign up to set email alerts
|

Low-Load Resistance Exercise Improves Cognitive Function in Older Adults

Abstract: Introduction: Resistance exercise (RE) training is widely recommended for increasing muscle strength and mass in older adults. RE is also a potential stimulus to improve cognitive functions (CF), but the best protocol for this purpose is unknown. Objective: To compare the effects of different RE protocols on CF in the same group of individuals. Methods: Twenty-four older adults were randomized (cross over) to control (CON) and lower limb RE protocols with high load (HL - 80% of 1RM), low load (LL - 30% of 1RM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Also, for resistance training with BFR, a first investigation by Sardeli et al [ 143 ] had observed positive effects on cognitive functions (Stroop-test) immediately after a low-load resistance training with BFR (30% of 1RM) [ 143 ]. Except for this first investigation of Sardeli et al [ 143 ], there are to our knowledge currently no further studies available (neither short-term nor long-term study) which directly examine the effects of localized hypoxic exposure on cognitive performance.…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%
See 2 more Smart Citations
“…Also, for resistance training with BFR, a first investigation by Sardeli et al [ 143 ] had observed positive effects on cognitive functions (Stroop-test) immediately after a low-load resistance training with BFR (30% of 1RM) [ 143 ]. Except for this first investigation of Sardeli et al [ 143 ], there are to our knowledge currently no further studies available (neither short-term nor long-term study) which directly examine the effects of localized hypoxic exposure on cognitive performance.…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%
“…Also, for resistance training with BFR, a first investigation by Sardeli et al [ 143 ] had observed positive effects on cognitive functions (Stroop-test) immediately after a low-load resistance training with BFR (30% of 1RM) [ 143 ]. Except for this first investigation of Sardeli et al [ 143 ], there are to our knowledge currently no further studies available (neither short-term nor long-term study) which directly examine the effects of localized hypoxic exposure on cognitive performance. Based on the first hint that localized hypoxia is beneficial for cognition, we want to outline several reasons why localized hypoxia during a resistance training (e.g., trough BFR) might be a promising intervention strategy which is likely to increase the efficiency of resistance training regarding the enhancement of cognitive functions in the following:…”
Section: Resistance Training With Blood Flow Restriction—an Added mentioning
confidence: 99%
See 1 more Smart Citation
“…70% of the 1 repetition maximum [1RM]) (5), a number of systematic reviews and meta-analyses demonstrated that low-load resistance training (20-30% 1RM) with BFR can induce similar gains in muscle mass and slightly less, but comparable improvements in strength in healthy young (56,99) and older adults (19,56) as well as in patients undergoing rehabilitation (37,57). Furthermore, research has shown that the application of BFR does not only increase muscle size and strength, but may also positively influence angiogenesis (6), vascular/endothelial function (35,97), bone health (13,44), cognitive function (94,105), and pain perception (39,48,49). For instance, studies have revealed that BFR training can also be used as a sufficient training method to induce cardiovascular (e.g., increased maximal oxygen uptake) (1,4,11,86) as well as functional and perceptual improvements (e.g., increased physical function, strength, and reduced pain) (25,40,51).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have analyzed the effects of moderate load resistance training (MLRT) in cognitive function and physical performance of elderly subjects; however, it is not clear how, or if, BFRRT alters the cognitive function in older individuals. A recent study investigated the acute effects of BFRRT on cognitive function of elderly, using the Stroop test, and have reported that a single BFRRT session (composed of 4 sets, being 1 of 30 repetitions and 3 of 15 repetitions, with 30% of 1RM and 50% total blood flow restriction) was able to reduce the execution time of the test, indicating an improvement in the cognitive function 7 .…”
Section: Introductionmentioning
confidence: 99%